THE CONCEPT OF ETHICS: RESPONSIBILITY OF THE MANGGARAI PEOPLE IN THE OKE DARA TA'A RITUAL ACCORDING TO EMMANUEL LEVINAS' PERSPECTIVE - Mathias Jebaru Adon; Pandor, Pius; Endi, Yohanes; Charles Virgenius Setiawan (Penamas, 2025)
The Manggarai community is increasingly concerned about the erosion of their local wisdom, particularly the awareness of relationships with others, nature, and the Creator. This decline is reflected in the rise of gang fights, tribal conflicts, and natural disasters, leading to a loss of togetherness and responsibility. Despite this, the Manggarai possess valuable wisdom on living together peacefully and fairly, expressed through art, literature, social systems, rituals, and religious ceremonies. This study explores the ethics of responsibility within the Manggarai community, focusing on the Oke Dara Ta’a ritual, and draws on Emmanuel Levinas’s philosophical framework. The Oke Dara Ta’a ritual is performed when someone dies unnaturally—through violence, accidents, disasters, or fights—to remove bad luck and protect other family members. The Manggarai believe that Dara Ta’a results from disharmony with others, ancestors, and the Creator. Levinas’s philosophy asserts that ethics arise from encountering the “face” of the other, which inherently demands responsibility. His ideas provide a lens to understand the ethical responsibility embodied in the Oke Dara Ta’a ritual. This qualitative study uses interviews with traditional leaders and ritual practitioners, grounded in phenomenological philosophy. The research highlights the significance of Manggarai local wisdom in fostering social and ethical responsibility